Clinical Management of a Patient with Chronic Recurrent Vertigo Following a Mild Traumatic Brain Injury - Eric G. Johnson (Case Reports in Medicine)
Vertigo, was provoked and right torsional up-beat nystagmus was observed in a 47-year-old patient when she was placed into the right Hallpike-Dix test position using infrared goggle technology. The clinical diagnosis was benign paroxysmal positional vertigo (BPPV), specifically right posterior canalithiasis, resulting from a mild traumatic brain injury (TBI) suffered approximately six-months earlier. Previous medical consultations did not include vestibular system examination, and Meclizine was prescribed to suppress her chief complaint of vertigo. Ultimately, the patient was successfully managed by performing two canalith repositioning maneuvers during a single clinical session. The patient reported 100% resolution of symptoms upon reexamination the following day, and the Hallpike-Dix test was negative. Continued symptom resolution was subjectively reported 10 days postintervention via telephone consultation. This case report supports previous publications concerning the presence of BPPV following TBI and the need for inclusion of vestibular system examination during medical consultation.